122k views
18 votes
Which of the following solutions solves the system?

Which of the following solutions solves the system?-example-1

2 Answers

0 votes
Answer: C) (1, -1)

Explanation:

Solving by Substitution Method :-

=> 7x + y = 6 (Eq. 1)
=> x + 2y = -1 (Eq. 2)

Therefore, from Eq. 2 :-

=> x = -1 - 2y (Eq. 3)

Substitute value of ‘x’ in Eq. 1 :-

=> 7x + y = 6
= 7(-1 - 2y) + y = 6
= -7 - 14y + y = 6
= -14y + y = 6 + 7 = 13
= -13y = 13
=> y = 13/-13 = -1

Therefore, y = -1

Substitute value of ‘y’ in Eq. 3 :-

=> x = -1 - 2y
= x = -1 - 2(-1)
=> x = -1 + 2 = 1

Therefore, x = 1

Hence, x = 1, y = -1 (1, -1)
User Oula Alshiekh
by
5.4k points
8 votes

(1,-1)

Explanation:

y=6-7x____put in the other equation

x+2(6-7x)=-1

x=1 and y=-1

User Kyle Brandt
by
5.2k points